The Influence of H5P Interactive Video on Stereoisomer Understanding in Terms of Learning Style - Kartimi, K.; Chandra, E.; Riyanto, O. R. (Jurnal Pendidikan IPA Indonesia, 2023)
The study aims to find differences in understanding of stereoisomers using h5p interactive videos based on student learning styles. The research method used was quasi-experimental, with a one-group posttest-only design. This study’s subjects were all second-year biology teacher education students at IAIN Syekh Nurjati Cirebon. The data were analyzed using descriptive and two-way ANOVA tests to determine differences in understanding. Future research is suggested to include more interactive video features in learning scenarios and measure other cognitive topics. The study found differences in stereoisomer understanding based on interactive videos and learning styles. There is no relationship between interactive video interaction and learning style and stereoisomer understanding simultaneously. This study is limited to the use of H5P interactive video. Subsequent work can increase the intensity and optimize the use of all H5P interaction features.